Waqf-Based Halal Tourism Development Strategy From the Aspect of Islamic Financial Institutions - Huda, Nurul; Rini, Nova; Nasution, Atiqi Chollisni; Masrizal, Masrizal; Rofi'i, Muhammad (ZISWAF, 2024)
The modern halal industry is not just associated with the food industry, but also with the tourism sector. In light of Islamic Financial Institutions, the objective of this study is to identify solutions for advancing waqf-based halal tourist development.  This study employs a qualitative methodology based on the Analytic Networking Process (ANP). Academics, practitioners, and regulators in the fields of halal tourism and waqf served as this study's expert informants.The primary obstacle to the growth of waqf-based halal tourism in Islamic financial institutions is the issue of innovation in Islamic financial products, namely innovation in funding goods derived from productive waqf. Access to Islamic finance through simplified administrative procedures for halal tourist MSMEs is the most effective answer to this challenge. The research findings have led to the creation of laws by the Indonesian Waqf Board and the OJK for Islamic financial institutions in Indonesia. The rule would include particular contracts for funding items for small and medium-sized enterprises (SMEs) in the halal tourist industry, as well as funding sources from waqf income. This study focuses exclusively on the halal tourist industry within the context of waqf-based development by Islamic financial institutions.